Knowing the city: maps, mobility and urban outreach work. (June 2014) - Hall, Tom; Smith, Robin J
This article is concerned with the relationship between (pedestrian) movement and (local) knowledge. Drawing upon ethnography conducted with a team of urban outreach workers, the article considers mapping, and specifically the use of Global Positioning System technology, as a method with which to document the spatial distribution of the team's practice as they search for and locate their rough-sleeping client group. Outreach workers are experts in the terrain in which they operate; maps of their movements, therefore, might be said to entail a mapping of knowledge, enacted in movement, and our informants do not move randomly, but knowledgeably. Our argument, however, grounded in an attention to the way in which knowledge and movement combine in the street-level practices of urban outreach, provides a foundation for a critique of mapping as an analytic practice in and through which relations of knowing and going can be shown and understood.